Urinary angiotensinogen is a marker for tubular injuries in patients with type 2 diabetes - Terami, Takahiro (Dove Medical Press, 2013)
PURPOSE: Urinary angiotensinogen has been reported as a marker for the activation of intrarenal renin–angiotensin system (RAS) in various kidney diseases. To investigate the importance of urinary angiotensinogen in diabetic nephropathy, we compared the urinary levels of angiotensinogen, albumin, and α1-microglobulin. MATERIALS AND METHODS: Japanese patients with type 2 diabetes at various stages of nephropathy (n=85) were enrolled, and we measured albumin/creatinine ratio (ACR) and urinary excretion of angiotensinogen and α1-microglobulin. We also compared the clinical data of the patients treated with or without angiotensin II receptor blockers or angiotensin-converting enzyme inhibitors (RAS inhibitors [+], n=51; RAS inhibitors [−], n=34). RESULTS: Urinary angiotensinogen levels positively correlated with ACR (r=0.367, P=3.84×10(−4)) and urinary α1-microglobulin (r=0.734, P=1.32 × 10(−15)), while they negatively correlated with estimated glomerular filtration ratio (eGFR) (r=−0.350, P=1.02 × 10(−3)) and high-density lipoprotein cholesterol (r=−0.216, P=0.049). Multiple regression analysis was carried out to predict urinary angiotensinogen levels by employing eGFR, ACR, and urinary α1-microglobulin as independent variables; only urinary α1-microglobulin entered the regression equation at a significant level. Although ACR was higher in the RAS inhibitors (+) group, urinary α1-microglobulin and angiotensinogen did not show significant increase in the RAS inhibitors (+) group. CONCLUSION: Urinary angiotensinogen is well correlated with urinary α1-microglobulin and reflected the tubular injuries which may be associated with the intrarenal RAS activation in patients with type 2 diabetes.